Nursing Workforce Analysis and comparison in the Non-Invasive Cardiac Diagnostic Units: Calculation Using Full Time Equivalents (FTEs) - Charoensin, Chantana; Srichai, Rachanee; Saeheng, Kanchana (Thammasat University Hospital Journal Online, 2025)
Background: Non-invasive cardiac diagnostic services require specialized nursing expertise. Appropriate nursing staffing levels are crucial for efficient and high-quality care delivery, especially for complex procedures. Inadequate staffing or improper workforce allocation may negatively impact patient care quality. Objectives: 1) To analyze nurse staffing based on workload in the non-invasive cardiac diagnostic unit at Songklanagarind Hospital; 2) To compare required staffing based on the Full Time Equivalents (FTEs) with current staffing levels. Methods: A descriptive study was conducted from February to July 2024, involving 23,209 patients, 3 registered nurses (RNs), and 12 other assistants (OAs, rotating 4 daily). Data was collected using a time-recording tool for procedures (CVI=0.86, ICC=0.845) and clinic statistics. FTEs were calculated from a total workload of 8,010.6 hours/year and compared with the Nursing Council’s standards (RN:PN ratio 70:30). Results: The average workload was 34.83 hours/day, with 100.91 patients/day. The unit required 5.72 FTEs (4 RNs, 2 PNs) or 6 RNs without PNs. Currently, it has 3 RNs and 4 OAs. The most time-intensive procedures were Dobutamine Stress Echocardiogram (3:36:30 hours/case) and Echocardiography (2,451:39:00 hours/year). Conclusion: The absence of practical nurses (PNs) results in excessive RN workload, potentially compromising care quality. Recommendations include increasing RNs/PNs per the 70:30 ratio, training OAs for basic tasks, and developing comprehensive workload analysis tools to enhance healthcare system sustainability.